2013
DOI: 10.1177/1933719112459218
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Rising CA-125 Levels Within the Normal Range in Patients With Uterine Papillary Serous Cancer

Abstract: The utility of cancer antigen 125 (CA-125) levels as an adjunct method of monitoring patients with uterine papillary serous carcinoma (UPSC) or endometrial serous carcinoma after surgery and adjuvant treatment has been reported. Our goal was to determine the significance of rising CA-125 levels within the normal range in these patients in the posttreatment surveillance setting. All patients with UPSC who underwent surgical staging and had preoperative CA-125 measurement from 1999 to 2008 were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…3,20Y25 Also, the rise in CA-125 in the reference range was associated with recurrence. 26 In our present study, the preoperative serum CA-125 level was found to be a preoperative predictive risk factor for LN metastasis. This factor may therefore help to subgroup UPSC patients and identify cases who should definitely undergo comprehensive staging surgery.…”
Section: Discussionsupporting
confidence: 55%
“…3,20Y25 Also, the rise in CA-125 in the reference range was associated with recurrence. 26 In our present study, the preoperative serum CA-125 level was found to be a preoperative predictive risk factor for LN metastasis. This factor may therefore help to subgroup UPSC patients and identify cases who should definitely undergo comprehensive staging surgery.…”
Section: Discussionsupporting
confidence: 55%
“… 7 Consistent with the current literature, our data showed that elevated serum CA 125 level was associated with advanced stage and recurrent disease. 24 , 25 Therefore, women with elevated preoperative CA 125 levels may benefit from this comprehensive staging.…”
Section: Discussionmentioning
confidence: 99%
“…CA‐125 can be used in the follow‐up of patients with high‐grade tumors and serous histology, as long as these tumors are altered at the time of diagnosis …”
Section: Resultsmentioning
confidence: 99%
“…[80][81][82] CA-125 can be used in the follow-up of patients with high-grade tumors and serous histology, as long as these tumors are altered at the time of diagnosis. 83 For patients with stage III and IV disease, chest, abdominal, and pelvic CT scans should be performed every 6 months for the first 3 years and every 6 to 12 months for the next 2 years. 84 Pelvic MRI can be performed in patients with persistent EC after 6 months with or without treatment failure.…”
mentioning
confidence: 99%